Analysis of Feedback Responsiveness on Employee Performance - Daffaessa Firgie; Zahra Aurela Lunanda; Firman Subarkah; Bima Aji Putra; Narumi Oktaviana (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Feedback has a central role in Human Resources (HR) management, because it is an important tool in helping employees reach their maximum potential. This study adopts a quantitative approach to explore the relationship between feedback responsiveness and employee performance in service companies in South Jakarta. Data were collected from 120 employees using purposive sampling method from February to March 2023. Statistical analysis indicates a significant relationship between feedback responsiveness and employee performance. The results show that high feedback responsiveness positively affects employee performance, highlighting the importance of effective communication and constructive feedback in the workplace. These findings support management theories emphasizing the crucial role of feedback in enhancing motivation, job satisfaction, and employee performance. Additionally, this study integrates findings from previous research to enrich understanding of this relationship in the context of the service industry in South Jakarta. In conclusion, these results provide valuable insights for HR practitioners and other stakeholders in evidence-based decision-making in dynamic business environments.